THE CENTRAL BANK AND FINANCIAL MARKET - Bejatović, Milorad (Law - Theory and Practice, 2010)
To be successfully carried out the transition of one economic system, it is necessary an existence of a developed system of institutions, that will be controlled by the central bank, which in the example of Serbia and Montenegro can not be sad, which occurs as a consequence for the lack of strong domestic banks,that would absorb a larger amount of money of one that is needed, that appears in the economic system as a result of large foreign direct investments that are larger than it is necessary, resulting in negative impact on the general price level or inflation. Financial markets are the intermediaries that performs ownership transformation, which is one of the basic prerequisites for successful transition process. Underdevelopment of financial instruments on the market of SCG leads to the inability for successful business of financial institutions and thereby to the disabling of the transition process through the financial system, which is only valid and real possible.